Parental well-being, couple relationship quality, and children's behavioral problems in the first 2 years of life. (August 2020) - Hughes, Claire; Devine, Rory T.; Mesman, Judi; Blair, Clancy; ,
Abstract: Adverse effects of early exposure to parental mood disturbance on child adjustment have been documented for both mothers and fathers, but are rarely examined in tandem. Other under-researched questions include effects of changes over time in parental well-being, similarities and contrasts between effects of parental mood disturbance on children's internalizing versus externalizing problems, and potential mediating effects of couple relationship quality. The current study involved 438 couples who reported symptoms of depression and anxiety at each of four time points (i.e., last trimester of pregnancy and 4, 14, and 24 months postbirth). Mothers and fathers also rated their couple relationship quality and their child's socioemotional adjustment at 14 months, as well as internalizing and externalizing problems at 24 months. Latent growth models indicated direct effects of (a) maternal prenatal well-being on externalizing problems at 24 months, and (b) paternal prenatal well-being on socioemotional problems at 14 months. Internalizing symptoms at 24 months showed only indirect associations with parental well-being, with couple relationship quality playing a mediating role. Our findings highlight the importance of prenatal exposure to parental mood disturbance and demonstrate that, even in a low-risk sample, poor couple relationship quality explains the intergenerational stability of internalizing problems.